Factors Affecting the Effectiveness of Assurance Services and Corporate Reporting - Ikechi, Joseph, Fineboy; Obinna, Nwaigburu, Kingsly; Onyinyechi, Omodero, Cordelia (International Journal of Economics, Business and Management Studies, 2019)
The study examines the issues affecting the effectiveness of assurance services and corporate reporting in Nigeria. The study uses a simple random technique, collection of primary data with questionnaire and testing of the hypotheses are done using percentage and Spearman’s Rank correlation coefficient. The results from the tests with the help of SPSS show positive and weighty relationship between integrity and honesty of external auditors and quality of assurance services and corporate reporting. The findings reveal that there is a significant correlation between impaired external auditor’s independence and quality of assurance services and corporate reporting. The more the independence of external auditors is impaired; the more ineffective the reliability of assurance services and corporate reporting. The study also reveals that there is a strong positive correlation between external auditor’s skills on the use of ICT facility such as computer and effective assurance services and corporate reporting. Hence, for effective assurance services and corporate reporting on the financial statement to be achieved, integrity and honesty of the auditor must be given preference. In addition to ensuring the independence of external auditors, they should be ICT compliant in order to embrace automated accounting system in line with digitalization developments in assurance services and corporate reporting. Thus, the study recommends that auditors should be meant to possess integrity and honesty, assume a high degree of independence and acquire proficiency in relation to ICT, based on computer based-auditing in order to achieve effectiveness, reliability and validity of assurance and corporate reporting services.